Factors Impacting Selection of Infectious Disease Training for Military Internal Medicine Residents. (4th October 2017) - Barsoumian, Alice; Hartzell, Joshua; Bonura, Erin; Whitman, Timothy J; Ressner, Roseanne; Yun, Heather
Abstract: Background: Applications to infectious disease (ID) fellowships have declined recently; however, the military has not noticed this trend. In the past 5 years, 3 US military programs had 47 applicants for 40 slots. Differences in military fellowships include tropical medicine emphasis, a required overseas experience, higher fellowship salary, and a 3 year Army training program. Practicing internists are also frequent applicants. A national survey of graduating internal medicine (IM) residents identified factors influencing career choice, including mentorship and salary. This study examines military IM residents to identify any differences. Methods: The prior survey tool was adapted to include questions unique to the training and practice of military medicine and uploaded onto an on-line survey platform. Program directors from 11 military IM residencies were asked to distribute survey links to their PGY-3s in Dec 16 – Jan 17. Data were categorized by ID interest and analyzed with Pearson's chi square or Fisher's exact as appropriate. Results: Response rate was 51% ( n = 68). 7% of respondents were ID applicants, 40% considered ID but reconsidered, and 53% were uninterested. No difference among the categories was seen with residency characteristics, length of military commitment, when interest in their field developed, or in timing of first ID rotation. 73% of those who considered ID changed their mind in their PGY-2/3 years. Primary deterrents from ID were salary (22%), lack of procedures (18%), and training length (18%). 60% of ID applicants were most drawn to global health or military ID. 12 respondents free texted that earlier exposure to the opportunities in ID may impact their decision. Conclusion: Despite differences in context of training and practice among military trainees compared with civilian colleagues, similar factors impact their career choice selection and decision to go into ID. Salary continues to be identified as a deterrent. Military residents also identified length of training and lack of procedures as major deterrents. Respondents suggested earlier exposure to the opportunities of ID may be a recruiting tool. Further studies are needed to determine what may influence residents during their last 2 years of training to consider pursuing ID. Disclosures: H. Yun, American Board of Internal Medicine, Infectious Disease Board: Board Member, travel reimbursement, honorarium